Describing immune factors associated with Hepatitis B surface antigen loss: A nested case-control study of a Chinese sample from Wuwei City - Yuan, Xiaojie; Fu, Ting; Xiao, Lixin; He, Zhen; Ji, Zhaohua; Seery, Samuel; Zhang, Wenhua; Ye, Yancheng; Zhou, Haowei; Kong, Xiangyu; Zhang, Shuyuan; Zhou, Qi; et al. (Frontiers in Immunology, 2022)
Background Hepatitis B surface antigen (HBsAg) loss is considered a functional cure for chronic Hepatitis B (CHB) although, several factors influence HBsAg loss. Methods 29 CHB had achieved HBsAg loss was selected and 58 CHB with persistent HBsAg were matched according to gender and age (+/- 3 years). Logistic regression model and restricted cubic spline (RCS) model was performed. Results Multivariate-adjusted logistic regression model which utilized stepwise selection showed that HBsAg levels negative correlate with HBsAg loss (odds ratio [OR] = 0.99, 95% confidence interval [CI] = 0.98-0.99). HBV vaccine history positively related with HBsAg loss (OR = 6.18, 95%CI = 1.14-32.54). After adjusting for age, HBsAg level, ALT level, HBeAg status, treatment and vaccine history, MMP-1 (OR = 0.66, 95%CI = 0.45-0.96), CXCL9 (OR = 0.96, 95%CI = 0.93-0.99), CXCL11 (OR = 0.77, 95%CI = 0.60-0.99) and TNF-R1 (OR = 0.96, 95%CI = 0.93-0.99) levels negatively related to HBsAg loss, respectively. Our multivariate-adjusted RCS model showed CXCL10 was associated with HBsAg loss in a “U-shaped” pattern. Conclusions Cytokines such as MMP-1, CXCL9, CXCL10, CXCL11 and TNF-R1 are important factors influencing HBsAg loss. It may be possible to develop a nomogram which intercalates these factors; however, further research should consider immune processes involved with HBsAg loss.